Staying and shifting patterns across IGT trials distinguish children with externalizing disorders from controls - Sallum, Isabela; Mata, Fernanda; Malloy-Diniz, Leandro F.; Miranda, Debora M. (Frontiers in Psychology, 2013)
The Iowa Gambling Task (IGT) is the most widely instrument used in the assessment of affective decision-making in several populations with frontal impairment. The standard performance measure on the IGT is obtained by calculating the difference between the advantageous and the disadvantageous choices. This standard score does not allows the assessment of the use of different strategies to deal with contingencies of gain and losses across the task. This study aims to compare the standard score method used in IGT with a method that analyses the patterns of staying and shifting among different decks across the 100 choices, considering contingencies of choices with and without losses. We compared the IGT performance of 24 children with externalizing disorders (Attention Deficit Hyperactivity Disorder and Oppositional Defiant Disorder) and 24 healthy age-matched children. The analyses of the standard score across all blocks failed to show differences among children with externalizing disorders and control children. However, healthy children showed a pattern of shifting more from disadvantageous decks to advantageous decks and choosing more consecutive cards from the advantageous decks across all blocks, independently of the contingency of losses. On the other hand, children with externalizing disorders presented a pattern of shifting more from advantageous decks to disadvantageous ones in comparison to healthy children and repeatedly chose cards from the B deck across all blocks. This findings show that even though differences among groups might not be found when using the standard analyses, a different type of analysis might be able to show distinct strategies on the execution of the test.